Influences of environmental change on the eco-evolutionary dynamics of an insular bird Zosterops lateralis - Sandvig, E (2018)
The colonisation of islands exposes species to novel biotic and abiotic conditions, that can produce convergent adaptations in morphological and life history traits. One phenotypic pattern, the “island rule”, states that initially large bodied species evolve smaller body sizes on islands and smaller species become larger. The underlying mechanisms for this pattern are likely to be complex, and depend on demographic variables and interactions among different phenotypic traits. In this thesis I evaluate mechanisms that may explain evolution of larger body sizes in insular birds by examining the influence of intrinsic and extrinsic factors on morphological and life history traits, and population dynamics of an insular passerine bird, using empirical and modelling approaches. Examining growth, a key determinant of body size, I found that altricial birds tend to grow slower on islands. Intriguingly, a simple integral projection model I analysed showed that the optimal pathway to larger body size was to grow faster. However, the model did not account for more subtle processes, such as within-individual optimisation of resource allocation. This is possibly occurring, as nestling growth variation was not proportional to parental care expenditure. Additionally, larger nestlings and juveniles had higher survival, while survival for all age classes was density-dependent. My findings suggest that island birds may achieve large body sizes by prioritizing offspring quality through slower growth and that size advantages are particularly important at early life stages.